TL versus SL Implied Reader: Assessing Receptivity when Translating Children’s Literature - Sousa, Cristina (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractThe reader of a translated text is particularly important when the translation is intended for a young audience. The translation must take into account the cultural knowledge of the intended reader. This article applies to translation studies some of the concepts advanced by critics Wolfgang Iser and Wayne Booth within the theory of literary reception. It looks at the rapport between the translator and the author, the implicit translator and the implicit author, the implicit target reader and the implicit source reader. Based on examples taken from an adaptation of Dorrit by Charles Dickens and the Portuguese translation of the Wolves of Willoughby Chase Chronicles by Joan Aiken, the article seeks to examine the role of the translator in assessing receptivity of the text.